PEMANTAPAN NILAI-NILAI PANCASILA UNTUK MENCEGAH SIKAP INTOLERANSI DI SEKOLAH SLTA PABA BINJAI - Saiful Amir; Andy Hakim (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2018)
This study aims to determine the strengthening of Pancasila values to prevent intolerance in Binjai PABA high school students. This type of research is quantitative descriptive using the survey method. Data analysis techniques use percentage and score systems. The population and research sample amounted to 286, the results of data analysis were obtained 170. The results of the study were three stages: First, the stage of recognition and understanding, 84% of students understood the Pancasila material, the two stages of acceptance, namely the attitude accepted by students on the basis of conformity between material lessons delivered with reality or needs in relation to themselves and their surroundings. The result is 93% accordingly. Third, the stage of attitude internalization or integrating values into attitudes in the personality of students is a reference in behaving and acting in accordance with the values of the principles of Pancasila.